ИССЛЕДОВАНИЕ ВЫСШЕЙ НЕРВНОЙ ДЕЯТЕЛЬНОСТИ У ЛИЦ С СИНДРОМОМ ПСИХИЧЕСКОГО ИНФАНТИЛИЗМА - Иванов, Д. А. (Журнал психиатрии и медицинской психологии; № 1 (9) (2002): ЖУРНАЛ ПСИХИАТРИИ И МЕДИЦИНСКОЙ ПСИХОЛОГИИ, 2023)
It was used associative experiment for the research of the higher nervous activity of the youth with the syndrome of psychic infantilism. A great number of patients with the similar demographical and social conditions were received the most serious research. It was obtained the typical changes of associative connections depending on forms of display the syndrome of psychic infantilism on the basic that were determined various dynamic disorder of the higher nervous activity of the patients